The role of pretreatment in improving the enzymatic hydrolysis of lignocellulosic materials - Sun, Shaoni; Sun, Shaolong; Cao, Xuefei; Sun, Runcang (Bioresource technology, 2016)
•The structure and factors constrain the digestibility of biomass were reviewed.•The features of the most important pretreatments were discussed.•Combined pretreatments were applied to optimize the utilization of lignocellulose.•Three combined pretreatments showed great potential for large-scale application. Lignocellulosic materials are among the most promising alternative energy resources that can be utilized to produce cellulosic ethanol. However, the physical and chemical structure of lignocellulosic materials forms strong native recalcitrance and results in relatively low yield of ethanol from raw lignocellulosic materials. An appropriate pretreatment method is required to overcome this recalcitrance. For decades various pretreatment processes have been developed to improve the digestibility of lignocellulosic biomass. Each pretreatment process has a different specificity on altering the physical and chemical structure of lignocellulosic materials. In this paper, the chemical structure of lignocellulosic biomass and factors likely affect the digestibility of lignocellulosic materials are discussed, and then an overview about the most important pretreatment processes available are provided. In particular, the combined pretreatment strategies are reviewed for improving the enzymatic hydrolysis of lignocellulose and realizing the comprehensive utilization of lignocellulosic materials.